A rare case of bilateral carotid body tumor with post-operative high vagal palsy - Chandu, Yadlapalli Sarath; Surushe, Shruthi (Indian Journal of Case Reports, 2024)
This case report details a rare instance of bilateral carotid body tumors (CBTs) in a 32-year-old female, emphasizing the clinical presentation, diagnostic process, staged surgical intervention, and subsequent management of post-operative complications, notably high vagal palsy. CBTs, a subset of paragangliomas, are rare neuroendocrine tumors with less than 10% malignancy rate, and bilateral occurrences are particularly uncommon. The patient’s treatment involved staged excisions of the tumors, with the post-operative period marked by the development of high vagal palsy, leading to significant swallowing difficulties. This case underscores the complexity of managing bilateral CBTs, highlighting the need for meticulous surgical planning and post-operative care to mitigate neurological complications. The report advocates for further research to enhance the understanding and management of such rare tumors.